2021
DOI: 10.3390/cancers13020339
|View full text |Cite
|
Sign up to set email alerts
|

Radiomics and Dosiomics for Predicting Local Control after Carbon-Ion Radiotherapy in Skull-Base Chordoma

Abstract: Skull-base chordoma (SBC) can be treated with carbon ion radiotherapy (CIRT) to improve local control (LC). The study aimed to explore the role of multi-parametric radiomic, dosiomic and clinical features as prognostic factors for LC in SBC patients undergoing CIRT. Before CIRT, 57 patients underwent MR and CT imaging, from which tumour contours and dose maps were obtained. MRI and CT-based radiomic, and dosiomic features were selected and fed to two survival models, singularly or by combining them with clinic… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
27
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 34 publications
(30 citation statements)
references
References 57 publications
0
27
0
Order By: Relevance
“…Dosiomic is increasingly used in clinical studies aiming to improve the prediction of clinical outcomes, e.g., locoregional recurrence after IMRT for head and neck cancer [23] or local control after carbon-ion radiotherapy in skull-base chordoma [21]. Dosiomic features were analysed by machine learning for the prediction of acute-phase weight loss in lung cancer patients treated with radiotherapy [30].…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Dosiomic is increasingly used in clinical studies aiming to improve the prediction of clinical outcomes, e.g., locoregional recurrence after IMRT for head and neck cancer [23] or local control after carbon-ion radiotherapy in skull-base chordoma [21]. Dosiomic features were analysed by machine learning for the prediction of acute-phase weight loss in lung cancer patients treated with radiotherapy [30].…”
Section: Discussionmentioning
confidence: 99%
“…A second appealing development is introducing dosiomic features into Tumour Control Probability (TCP) and Normal Tissue Complication Probability (NTCP) models, thus overcoming the current limitation of these models [19]. Some authors recently employed dosiomics to improve the prediction of side effects [20][21][22] or local control after radiotherapy [23], including preliminary multicentre experiences [24]. The proposed dosiomic signatures must be highly stable and reproducible and need validation before being used in clinical practice.…”
Section: Introductionmentioning
confidence: 99%
“…In this regard, several research groups have also suggested to incorporate dosimetric deviations in targets and/or OARs (such as parotid glands) as part of the ART regimen (12,(18)(19)(20). Of note, although Dosiomics has recently been studied for prediction of toxicity (32,34,(41)(42)(43) and prognosis (33,44) in cancer patients, its potential in treatment response prediction, in particular on the basis of the RECIST criteria, has not been reported. Future studies in this aspect are recommended to confirm its capability in this regard.…”
Section: Discussionmentioning
confidence: 99%
“…Notably, the dosiomic features are not more powerful than the clinical parameters, but the combination of these two attributes substantially improves performance. Buizza et al (165) extended this method to rare tumors to assess LC after carbon-ion RT (CIRT) for skull-based chordomas (SBC) and noted that dosiomic signatures were the most promising traits compared with clinical variables, the profile of CT and MR, with comparable radiomic and clinical model capabilities. The studies by Murakami et al (164) and Buizza et al (165) yielded different conclusions when assessing the predictive power of dosiomic profiles and clinical factors, which may be associated with variations in radiation treatment regimens.…”
Section: Radiotherapy Prognosismentioning
confidence: 99%
“…Several recent studies have illustrated that dosiomics is also applicable in evaluating prognosis after radiotherapies, such as locoregional recurrences (LR) ( 163 ), biochemical recurrence (BCR) ( 164 ), and local control (LC) ( 165 ). An LR study in intensity-modulated RT (IMRT) for neck tumors indicated that the combined model based on features of CT, PET, and 3D dose distribution maps performed better than radiomics alone, suggesting that dosiomic characteristics are associated with LR and have prognostic value ( 163 ).…”
Section: Some Case Studies and Applicationsmentioning
confidence: 99%